(untitled) (Texas Journal of Agriculture and Biological Sciences, 2026)
The article examines the spatial distribution, landscape zonation, and ecological dependencies of representatives of the Scaritinae subfamily under the conditions of the Fergana Valley. The results indicate that species belonging to this subfamily are predominantly distributed in alluvial plains, riverbanks, and sandy-clay soils. It was also determined that their activity is significantly influenced by soil moisture, temperature, and anthropogenic factors.